A STUDY ON ANTIBIOTIC PRESCRIBING PATTERN IN OBSTRUCTIVE LUNG DISEASE INPATIENTS - R, Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The main objectives of this study were to estimate the demographic details of patients with obstructive lung disease and to study the various organisms causing exacerbations and its resistance pattern and also to analyze the culture and sensitivity pattern in obstructive lung disease patients. Methods: It was a retrospective, observational study carried out for 1 year at the Department of Pulmonary Medicine of a tertiary care teaching hospital in Kerala, India. Total 200 patients who were admitted under the pulmonary ward during the time period from 1 June 2014 and who satisfied the inclusion and exclusion criteria were included in the study. A standardized data collection form was prepared, and necessary data were collected from patient's medical records. Results: The maximum number of patients was in the age group of 60‑69. 61% patients were residing in the urban area. 32.5% of patients were found to have a history of smoking. 61% patients were diagnosed with the chronic obstructive pulmonary disease (COPD). 74.5% sample collected were sputum. Culture test alone was carried out for 48.5%. 88% were prescribed with cephalosporin. Among the cephalosporin class cefpodoxime was the most commonly prescribed (63%). 42 patients had two drug therapy. Conclusion: A periodic study on the usage of antibiotics and sensitivity pattern in the hospital will enable the health care professionals to select the appropriate one to promote the rational use of antibiotics. Key words: Asthma, Chronic obstructive pulmonary disease, Exacerbation, Antibiotics. st June 2013 to 1 st